Solution Processed Hybrid Photovoltaics - The Preparation of a Standard ZnO Template - Downing,J; Ryan,MP; Stingelin,N; McLachlan,MA (Journal of Photonics for Energy, 2011, 2011)
The formation of a well-defined, reproducible ZnO nanorod scaffolds for hybrid photovoltaic (h-PV) applications has been investigated. A standard hydrothermal growth method was used and the influence of chemical additions in controlling length, width, density and orientation was studied. The nanostructures prepared have been characterised by scanning electron microscopy, X-ray diffraction, UV-Vis spectroscopy in addition to measurement of the wetting behaviour. A standard procedure for the production of vertically orientated nanorods with a narrow size distribution, high areal density and good wettability in aqueous solutions is presented.